Clinical Perspective of Myocardial Recovery and Improvement: Definitions, Prevalence, and Relevance - Anthony V. Pensa; Veronica Zheng; Lucia Davis; Rebecca W. Harap; Jane E. Wilcox (Methodist DeBakey Cardiovascular Journal)
Partial or complete imaging resolution of left ventricular (LV) systolic dysfunction in patients with heart failure with reduced ejection fraction (HFrEF) has gone by many names in the past few decades, including LV recovery, remission, reverse remodeling, and, most recently, improvement. This phenomenon has been described in a variety of clinical scenarios, including removal of an acute myocardial insult, unloading with durable LV assist devices, and treatment with various devices as well as pharmacotherapies, termed guideline-directed medical therapy (GDMT). Irrespective of definition, systolic improvement is associated with improved clinical outcomes compared to persistent systolic dysfunction. In the past few years, systolic improvement has been distinguished from HFrEF as a new clinical entity referred to as HF with improved EF (HFimpEF). Given the relative novelty of this condition, there is a paucity of data with regard to the clinical trajectory and management of this population. In this review, we describe the history of myocardial improvement terminology and explore notable findings that have led to the delineation of HFimpEF. Additionally, we highlight the importance of understanding LV trajectory and the potential opportunity for new GDMT management for clinicians when treating patients with HFimpEF.